Analisis Kadar COD dan BOD pada Air Sumur Akibat Buangan Limbah Pabrik Tapioka di Kec.Pallangga Kab. GOWA - Nurhalisa Nurhalisa; Ardiansah Hasin (Jurnal Media Laboran, 2017)
Water is a basic need for human life that is used as drinking water, food additives, as irrigation and as a household need so it is necessary to know the content of the water. Various water sources used for daily needs such as well water can be polluted by waste containing COD and BOD. COD and BOD can cause symptoms of health problems such as typhoid, cholera, dysentery, and even death. This study aims to identify and determine the levels of COD and BOD in well water around tapioca flour mills in Pallangga District, Gowa Regency. The sampling technique in this study was purposive sampling. There were 2 wells which were the sampling points around the tapioca flour mill, each well location was the closest distance to the tapioca flour mill. The results of the analysis of the levels of COD and BOD obtained in each COD were 40 mg / L and 80 mg / L while in BOD it was 12.8 mg / L and 19.2 mg / L. All well water samples tested by COD and BOD were not obtained levels that exceeded the maximum level.